Never and forever - Cowell, Cressida (Cowell, Cressida. Wizards of once (Series), 2020)
The author of How to Train Your Dragon returns with the final, magical installment of the New York Times bestselling Wizards of Once series! Xar and Wish are on the final leg of their journey -- first stop: The Mine of Happiness. Here, starvation is never far away for the Magical creatures who toil in its horrible depths. Xar and Wish must escape and fast; Xar needs to take control of his ever-growing Witchstain, and Wish must achieve her Destiny. But the Tazzelwurm is in their way, a grotesque monster who threatens to block every entrance. Time is not on their side, but the forests are calling them. Will their combined strength be enough for the biggest quest so far: to defeat the Kingwitch once and for all?